Conventional and islamic stock markets: what about financial performance? / Aymen Ben Rejeb and Mongi Arfaoui - Rejeb, Aymen Ben; Arfaoui, Mongi (Universiti Teknologi MARA Selangor, 2017)
The main objective of this paper is to analyse the performance of both Islamic and conventional stock market indices, particularly during the financial subprime crisis period. For this purpose, we use updated data including the recent financial instability periods and a relevant methodology based on the time varying parameter model combined with a GARCH specification, a Granger non-causal test and a structural break points technique. The empirical results show that the weak efficiency hypothesis is relatively verified in the Islamic context than in the conventional one. Moreover, we can conclude that Islamic markets are not fully immunised against the effects of financial crises and the strong financial fragilities. The results of the Granger non-causality test suggest that the Islamic stock markets have succeeded to relatively escape important part of the last subprime crisis harmful effects. This may encourage investment in this type of markets and therefore allows the strengthening of economic growth.